Dietary Intake and Food Habits of Pregnant Women Residing in Urban and Rural Areas of Deyang City, Sichuan Province, China - Gao, Haoyue; Stiller, Caroline K.; Scherbaum, Veronika; Biesalski, Hans Konrad; Wang, Qi; Hornmann, Elizabeth; Bellows, Anne C. (My University, 2013)
Micronutrient deficiencies and imbalanced dietary intake tend to occur during the reproductive period among women in China. In accordance with traditional Chinese culture, pregnant women are commonly advised to follow a specific set of dietary precautions. The purpose of this study was to assess dietary intake data and identify risk factors for nutritional inadequacy in pregnant women from urban and rural areas of Deyang region, Sichuan province of China. Cross-sectional sampling was applied in two urban hospitals and five rural clinics (randomly selected) in Deyang region. Between July and October 2010, a total of 203 pregnant women in the third trimester, aged 19–42 years, were recruited on the basis of informed consent during antenatal clinic sessions. Semi-structured interviews on background information and 24-h dietary recalls were conducted. On the basis of self-reported height and pre-pregnancy weight, 68.7% of the women had a pre-pregnancy body mass index (BMI) within the normal range (18.5 ≤ BMI < 25), 26.3% were found to be underweight with a BMI <18.5 (20.8% in urban vs. 35.6% in rural areas), while only 5.1% were overweight with a BMI ≥30. In view of acceptable macronutrient distribution ranges (AMDRs) the women’s overall dietary energy originated excessively from fat (39%), was low in carbohydrates (49.6%), and reached the lower limits for protein (12.1%). Compared to rural areas, women living in urban areas had significantly higher reference nutrient intake (RNI) fulfillment levels for energy (106.1% vs. 93.4%), fat (146.6% vs. 119.7%), protein (86.9% vs. 71.6%), vitamin A (94.3% vs. 65.2%), Zn (70.9% vs. 61.8%), Fe (56.3% vs. 48%), Ca (55.1% vs. 41%) and riboflavin (74.7% vs. 60%). The likelihood of pregnant women following traditional food recommendations, such as avoiding rabbit meat, beef and lamb, was higher in rural (80%) than in urban (65.1%) areas. In conclusion, culturally sensitive nutrition education sessions are necessary for both urban and rural women. The prevalence of underweight before conception and an insufficient supply of important micronutrients were more pronounced in rural areas. Therefore, attention must be given to the nutritional status, especially of rural women before, or at the latest, during pregnancy.
Keywords: Ernährung; Schwangerschaft; Stadt; Medizin; 610 Medizin und Gesundheit; Land; China